Interactive PowerPoint Media in Elementary Science Learning Outcomes: Media PowerPoint Interaktif dalam Hasil Pembelajaran Ilmu Pengetahuan Alam di Sekolah Dasar - Salsabila Maulidi Lafsa; Enik Setiyawati (Academia Open, 2025)
General Background Twenty-first century education requires the integration of digital learning media to support meaningful and student-centered instruction in elementary schools. Specific Background In elementary science learning, conventional teaching methods often limit student engagement and conceptual understanding, necessitating the use of interactive multimedia tools such as PowerPoint-based learning media. Knowledge Gap Although interactive media has been widely discussed, empirical evidence regarding its structured implementation in elementary science classrooms remains limited in specific school contexts. Aims This study aims to analyze the use of interactive PowerPoint media in science learning for elementary students and examine differences in student learning outcomes. Results The findings indicate that students taught using interactive PowerPoint media achieved higher post-test scores compared to their pre-test performance, demonstrating measurable differences in learning outcomes. Classroom observations also show increased participation and engagement during instructional activities. Novelty The study provides contextual empirical data on the structured integration of interactive PowerPoint media within elementary science instruction. Implications These findings suggest that interactive digital media can serve as a practical instructional alternative for science teachers seeking structured and technology-supported classroom practices. Keywords: Interactive PowerPoint, Science Learning, Elementary Education, Digital Learning Media, Learning Outcomes Key Findings Highlights: Post-test scores exceeded pre-test performance in science classes. Classroom participation increased during multimedia-supported instruction. Structured digital slides facilitated clearer concept delivery.